GIAKUSUKI PADA KARATE: ANALISI PERAN KEKUATAN OTOT LENGAN DAN OTOT BAHU: Indonesia - Adi Saputra, Surya (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2020)
The study purpose: To determine the relationship between hand muscle strength and shoulder muscle strength with the ability to punch straight ahead of Karate extracurricular members at SDN 07 Cipinang Melayu. Materials and methods: This research is a correlation study AND the population of this study is 20 students. The instruments used in this research are hand muscle strength using hand grib dynamometer or handheld dynamometer, for shoulder muscle strength survey using Expanding Dynamometer, to survey strokes with inner tube rubber bearings. Results: There is a significant relationship between hand muscle strength and the ability to hit straight ahead with t count 3.163>ttable 1.729, there is a significant relationship between shoulder muscle strength and straight forward punch ability with t count 2, 874>ttable 1.729, there is a relationship which is significant between hand muscle strength, shoulder muscle strength with the ability of a straight forward punch t count 5,311> ttable 3,125. Conclusions: There is a significant relationship between hand muscle strength, shoulder muscle strength and the ability to punch straight ahead of the Karate extracurricular members at SDN 07 Cipinang Melayu.